Work-Related Stress, Quitting Intentions and Absenteeism - Rannia M. Leontaridi; Melanie E. Ward (Institute for the Study of Labor (IZA), 2002)
The paper uses data from the International Social Surveys Program (ISSP) to investigate work-related stress among a group of 15 OECD countries. It examines the determinants of work-related stress and explores the importance of work-related stress as a predictor of individuals' quitting behaviour and the rate of absenteeism. We find that those individuals reporting to experience at least some stress in their current position are 10 - 14 % more likely to hold intentions to quit or be absent from work than those without any job stress, with the probability of intending to quit or being absent increasing with successively higher workrelated stress levels.
Keywords: I10; J28; J22; J63; 330; job stress; quits; turnover; absenteeism; Streß; Arbeitsmobilität; Fehlzeit; Schätzung; OECD-Staaten